Orthopaedic and trauma nursing : an evidence-based approach to musculoskeletal care - Clarke, Sonya; Drozd, Mary (Hoboken, NJ : John Wiley & Sons, Inc., 2023)
'A comprehensive and evidence-based manual for orthopaedic and trauma nurses and students In the newly revised second edition of Orthopaedic and Trauma Nursing: An Evidence-based Approach to Musculoskeletal Care, a team of accomplished practitioners and educators delivers a straightforward and practical handbook for the practice of adult, child and young people's orthopaedic and trauma nursing. The book explores topics of critical importance to those working in acute wards, clinics, community hospitals, nursing homes, and patients' homes. Divided into 5 intuitive sections, this book examines central issues in orthopaedic and musculoskeletal trauma care, specialist practice issues, the care and management of common conditions, and the care of infants, children and young people. Each chapter is based on the latest research and offers practical guidance to practitioners around the world'--
An introduction to orthopaedic and trauma care / Julie Santy-Tomlinson, Sonya Clarke and Mary Drozd -- The knowledge and evidence base for practice / Paul McLeish -- Professional development, competence and education / Mary Drozd and Sinead Hahessy -- The musculoskeletal system and human movement / Lynne Newton-Triggs and Jean Rogers -- The team approach and nursing roles in orthopaedic and musculoskeletal trauma care / Sandra Flynn -- Rehabilitation and the orthopaedic and musculoskeletal trauma patient / Rebecca Jester -- Clinical assessment of the orthopaedic and trauma patient / Rebecca Jester -- Key musculoskeletal interventions / Lynne Newton-Triggs, Jean Rogers and Anna Timms -- The complications of musculoskeletal conditions and trauma / Julie Santy-Tomlinson, Sonya Clarke and Peter Davis -- Nutrition and hydration / Rosemary Masterson -- Pain assessment and management in orthopaedic and trauma care / Carolyn Mackintosh-Franklin -- Wound management, tissue viability and infection / Jeannie Donnelly and Alison Collins -- Key conditions and principles of orthopaedic management / Elaine Wylie and Sonya Clarke -- Elective orthopaedic surgery / Rebecca Jester, Sandra Flynn and Mary Drozd -- Musculoskeletal oncology over the lifespan / Helen Stradling -- Principles of trauma care / Fiona Heaney, Yvonne Conway and Stefanie Cormack -- Principles of fracture management / Julie Craig, Sonya Clarke and Pamela Moore -- Fragility fractures / Julie Santy-Tomlinson and Karen Hertz -- Fragility Hip Fracture / Karen Hertz and Julie Santy-Tomlinson -- Spinal cord injury / Sian Rodger -- Soft tissue, peripheral nerve and brachial plexus injury / Julie Craig, Beverley Gray Linnecor and Martyn Neil -- Key issues in caring for the child and young person with an orthopaedic or musculoskeletal trauma condition / Sonya Clarke -- Common childhood orthopaedic conditions, their care and management / Julia Judd -- Fracture management in the infant, child and young person / Elizabeth Wright -- Key fractures relating to infant, child and young person / Thelma Begley and Sonya Clarke.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 25, 2023).
OCLC control number change
Keywords: Orthopedic nursing; Wounds and injuries -- Nursing; Evidence-based nursing; Orthopedic Nursing -- methods; Trauma Nursing -- methods; Musculoskeletal System -- injuries; Wounds and Injuries -- nursing; Evidence-Based Nursing